2019
DOI: 10.1007/s00402-019-03296-3
|View full text |Cite
|
Sign up to set email alerts
|

Greater activity, better range of motion and higher quality of life following unicompartmental knee arthroplasty: a comparative case–control study

Abstract: Purpose The purpose of this study was to provide a matched cohort comparison of clinical and functional outcome scores, range of motion and quality of life following unicompartmental knee arthroplasty (UKA) or total knee arthroplasty (TKA). The hypothesis was that patients receiving UKA report better results than comparable patients who receive conventional TKA. Methods Clinical and functional results of 35 patients with medial end-stage osteoarthritis who had received a fixed-bearing UKA were compared with th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
23
1
2

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(28 citation statements)
references
References 41 publications
2
23
1
2
Order By: Relevance
“…After screening the titles and abstracts, 44 related studies were first screened out. After conducting a full-text review on the remaining studies, 13 studies were left in the final analysis, including 4 RCTs and 9 non-RCTs (cohort and case-control studies) [3,5,9,12,13,[23][24][25][26][27][28][29][30].…”
Section: Study Selectionmentioning
confidence: 99%
“…After screening the titles and abstracts, 44 related studies were first screened out. After conducting a full-text review on the remaining studies, 13 studies were left in the final analysis, including 4 RCTs and 9 non-RCTs (cohort and case-control studies) [3,5,9,12,13,[23][24][25][26][27][28][29][30].…”
Section: Study Selectionmentioning
confidence: 99%
“…Blevins et al observed that UKA patients suffered less postoperative pain, achieved a higher KSS and were able to return to their workplace sooner than patients receiving TKA [ 18 , 27 ]. Hauer et al found an improvement in the Tegner Activity Scale (TAS) and a better ROM [ 19 ]. Even though there is a growing number of studies underlining the better clinical and functional outcome of UKA, there are also reports showing no benefit of UKA over TKA.…”
Section: Discussionmentioning
confidence: 99%
“…UKA is less invasive and retains more of the patient’s knee joint structure than TKA. UKA procedures can obtain good knee ROM earlier and easier than TKA[ 10 , 11 ]. Therefore, patellar fractures should not be regarded as a contraindication to UKA.…”
Section: Discussionmentioning
confidence: 99%